Structure-based design of peptide inhibitors for Protein Arginine Deiminase Type IV (PAD4) - Teo, Chian Ying; Ibrahim, Zalikha; Abdul Rahman, Mohd Basyaruddin; Tejo, Bimo Ario (ScienceDirect, 2018)
Protein Arginine Deiminase IV (PAD4) is a new target for rheumatoid arthritis (RA) therapeutic. The enzyme catalyzes the citrullination process in human body that produces citrullinated protein which is believed to be the root cause of RA. The search for inhibitor for the enzyme could lead to the discovery of drug for the treatment of RA. Peptide-based drugs attract attention from public for their attractive advantages such as high specificity and low toxicity in comparison to conventional small molecule drugs. As peptide is a natural substance, introduction of peptide-based drug to human body is believed to have less negative impact compared to small molecules. Strong binding between the peptide-based inhibitor to the receptor can be achieved by structure modification of the existing natural amino acids. Combination of the CADD techniques and peptide-based drug design can be a fascinating method in designing PAD4 inhibitors with strong binding and low toxicity properties. In this article, we explained our work on systematic design of peptide inhibitor for PAD4. Due to specific shape of PAD4 binding pocket, the anatomy of the peptide inhibitor must consist of the “backbone”, “neck” and “warhead” parts. We discovered that peptide inhibitors containing furan ring was the “warhead” show high potential in inhibiting PAD4 and the peptide can be modified to be a better drug candidate for treatment of rheumatoid arthritis.